Sociological rescues of the body: Outline of a conceptual path - Ferreira , Vítor Sérgio (2013)
This article will outline the conceptual route that resulted in the denaturalization of the body by sociology and the struggle for the body autonomy as an object of study and specific disciplinary area within this social science. The rescue of the body as mere biological organism dear to life sciences by sociology started with the elaboration of the concept of “corporeality”, positioning the body as a cultural construction located in time and space. The concepts of “incorporation” and “outcorporation” regard the paradigms that rescued the body as a place of exercise of power and that positioned it in the debate between structure and social action. The concept of “embodiment” rescues the body from the mere condition of inert “object” or “accessory” to which the more radical constructivists paradigms had confined it.